Resilient and efficient small ruminant value chains in the Mediterranean basin: challenges and opportunities from society and consumers’ needs - Zanoli R. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Mediterranean areas are characterized by a high proportion of sheep and goats in the total ruminant livestock units (30% vs 10% worldwide); such proportion is slowly decreasing, while it increases at a global level. A possible explanation is that small ruminant farming is mainly associated with traditional systems, which performance and resilience are limited in the present context. An interesting concept, introduced by Nassim Nicholas Taleb, is the notion of “anti-fragility”, which goes beyond resilience or robustness: an anti-fragile system does not only survive to the shocks it endures, it gets better after them. An anti-fragile sheep and goat value chain would: (i) focus on the right knowledge, which enables to detect, understand and endure the changes affecting the supply chain; (ii) adjust in real-time, in order to seize the chances of positive change; (iii) be based on a network approach, which is less fragile than a linear pipeline. A common fallacy of sheep and goat research in this respect is the low importance and priority which have been given, until recently, to innovation (in products, processes, marketing). Innovation could help answering strategic issues for Mediterranean areas: the remuneration of ecosystem services, a better compliance with agro-ecological principles, an improved access to the market for pastoral products. The change in the consumer landscape represents a major challenge for traditional sheep and goat value chains. In the Mediterranean basin, the population is concentrated near the coast while small ruminants are found mainly in the inner lands. The population is ageing and the time devoted to cooking meals has been reduced by half in the last 30-40 years. Lamb and goat meat is tasty and benefits from a natural, genuine, authentic image; though, it is usually rich in fat, requires a long cooking time and its strong taste has become unfamiliar to the younger generations. As a consequence, consumers increasingly prefer chicken or veggie meat. However, consumers are not all alike and market segmentation could help commercialise small ruminant meat. Collective brands, fancy packaging (small portions, with labels and illustrations) or ready-to-use (seasoned or cooked) products are promising strategies to increase sales for the small ruminant meat sector. In a reputation economy based on social media, advertising the products with the help of renowned chefs could help to make sheep and goat meat more trendy. This presentation focussed on meat, because at the present moment it is the most fragile component of sheep and goat value chains. Many PDOs exist for dairy products (cheese) and goat milk is highly demanded in Europe; still, logistic issues and a better organization of dairy supply chains should be addressed, especially in Southern Mediterranean countries. Because specialized systems are more fragile, a general issue in the future should be to encourage diversified systems, possibly based on dual-purpose breeds. And of course, organising supply chains and new, innovative, distribution channels.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)